The local stability of a compartmental corruption epidemic model under the impact of personal willingness - Muhafzan; Arrival Rince Putri; Noverina Alfiany; Hafizhah Artrya Hanan (Statistics, Optimization & Information Computing, 2025)
The given work establishes a compartmental corruption epidemic model that consists of the susceptible compartment, exposed compartment, corrupt compartment, jailed compartment, reformed compartment, and honest compartment under the impact of personal willingness. In this model, it is assumed that corruption spreads like an infectious disease if there is an interaction between a susceptible individual and a corrupt individual, hence the epidemiology theory can be used to analyze the behavior of the model. The local stability analysis of the model is established. The study shows that the corruption-free fixed point and the corruption-endemic fixed point depend on the basic reproduction number. The numerical simulations that demonstrate the local stability of the corruption-free fixed point and the corruption-endemic fixed point under influence of the personal willingness are conducted.